QUICK AND EASY METHODS OF LEARNING ENGLISH (Modern education and development, 2024)
Learning English quickly and effectively is a common goal for millions of learners worldwide, particularly in the context of globalization, where English has become the lingua franca of business, science, and technology. This article presents a comprehensive overview of practical, time-efficient methods for learning English, suitable for beginners as well as intermediate learners. Emphasis is placed on immersion techniques, active usage of the language, technological tools, mnemonic devices, and structured learning strategies. The article discusses the importance of daily practice, cultural exposure, vocabulary-building techniques, and the integration of listening, speaking, reading, and writing exercises. The goal is to provide learners with an actionable roadmap for mastering English in a short time, supported by modern language learning theories and tools.